The Influence of Heritage Image, Destination Image, and Experiential Quality on Behavioural Intentions of Foreign Tourists - Junarta, Harbyanto; Nuryakin, Nuryakin; Fatmawati, Indah (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2021)
This research examines heritage image model influence, destination image, experiential quality in influencing tourist behavioral intention in Mandalika Kuta beach Lombok. Mandalika Kuta beaches Lombok as the object, while the subject is foreign tourists. This research used the Purposive sampling method and 133 respondents as the sample. The tool analysis is using Structural Equation modeling/AMOS. The heritage image and destination image give positive influences to the tourist’s experiential quality; the experiential quality gives positive impacts to the tourist’s revisit intentions. The limitation of this study is that the time to conduct this study is limited, only one month. In addition, the indicators used in this study are limited. This research has a significant practical contribution; Some objectives still focus on providing product-oriented marketing and management practices.